EVALUATION OF DOUBLE-FACED TUBULARIZED PRENUPTIAL FLAP VERSUS DOCKETS PROCEDURE FOR REPAIR OF PENOSCROTAL HYPOSPADIAS REPAIR - ALI , R; BUMBIA , HA; SOOMRO , NH; MEMON , AH; ADNAN, MA; HIRAJ, GM (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to compare the outcomes of the double-faced tabularized preputial flap and Dockets procedure for repairing penoscrotal hypospadias. A retrospective analysis was conducted on 200 patients who underwent either a double-faced tubularized preputial flap or Dockets procedure for penoscrotal hypospadias repair between 2018 and 2022. These patients were partitioned into two gatherings given the careful method utilized: Group A (twofold confronted tubularized preputial fold) and Group B (Duckett strategy). Data was collected from 200 patients and divided into two groups. The success rates were similar between the two groups. In the double-faced tubularized preputial flap group, 94% of patients achieved successful outcomes. Similarly, 92% of patients achieved successful outcomes in the Duckett procedure group. The mean operative time in the double-faced tubularized preputial flap group was 107 minutes, whereas it was 132 minutes in the Duckett procedure group (p < 0.05). Both double-faced tubularized preputial flap and Dockets procedure are viable options for the repair of penoscrotal hypospadias. However, the double-faced tubularized preputial flap has a shorter operative time and a lower incidence of urethral strictures, while the Dockets procedure has a higher incidence of complications related to the scrotal skin flap. The choice of technique should be based on individual patient characteristics and surgeon preference.